2006
DOI: 10.1055/s-2006-944736
|View full text |Cite
|
Sign up to set email alerts
|

The role of wireless capsule endoscopy in investigating unexplained iron deficiency anemia after negative endoscopic evaluation of the upper and lower gastrointestinal tract

Abstract: This study demonstrates the importance of investigating the small bowel with WCE in patients with unexplained IDA after negative standard endoscopic evaluation. Wireless capsule endoscopy is superior to enteroclysis for detecting lesions of the small bowel in patients with unexplained IDA and should be the next diagnostic test of choice after unremarkable standard endoscopic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 19 publications
4
65
1
4
Order By: Relevance
“…Data suggest that AVMs may cluster within intestinal segments [16], and it is estimated that 40-60% of patients have more than one lesion [17,18]. Further, the reported prevalence of concurrent upper and lower GI tract lesions varies from ''rare'' to as high as 33% [16,[19][20][21][22]. As a result of this uncertainty, in patients with OGIB and known, but either previously treated or clinically insignificant upper and/or lower GI tract AVMs, the most appropriate diagnostic ''next step'' is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that AVMs may cluster within intestinal segments [16], and it is estimated that 40-60% of patients have more than one lesion [17,18]. Further, the reported prevalence of concurrent upper and lower GI tract lesions varies from ''rare'' to as high as 33% [16,[19][20][21][22]. As a result of this uncertainty, in patients with OGIB and known, but either previously treated or clinically insignificant upper and/or lower GI tract AVMs, the most appropriate diagnostic ''next step'' is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In one prospective study, the diagnostic yield of CE in patients with unexplained IDA was shown to be 57% (29/51 patients) with 1-year follow-up data showing resolution of IDA in all patients after medical or endoscopic treatment [5]. The aim of this study was to compare the yield of CE in patients referred for IDA to a control group with obscure overt GI bleeding and to determine long-term outcomes in patients with IDA post-VCE.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of CE are commercially available: PillCam SB1/2 (Given Imaging, Yokneam, Israel), EndoCapsule (Olympus Medical Systems, Tokyo, Japan), MiRo (IntroMedic, Seoul, Korea), and OMOM (Chongqing Jinshan Science & Technology Group, Chongqing, China). Typically, the recorder acquires approximately 50 000-60 000 images in 7-8 h. 11 The general indications for small bowel CE are overt or occult GI bleeding with iron defi ciency anemia, [12][13][14] Crohn's disease, 15,16 suspected small bowel tumor, 17 surveillance of inherited polyposis syndrome, 18 evaluation of abnormal small bowel imaging or drug-induced small bowel injury, 19 and celiac disease. The main contraindications for CE include known or suspected GI obstruction, stricture or fi stula, cardiac pacemaker or implanted electromedical devices, 20 and swallowing disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Capsule endoscopy (CE) and double balloon endoscopy have been reported to be useful in the diagnosis of small-intestinal bleeding. [9][10][11][12][13][14][15][16][17][18][19][20][21] This report describes a rare case of idiopathic ileal varices diagnosed by these modalities and treated by laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 95%